2014
DOI: 10.5194/acp-14-7195-2014
|View full text |Cite
|
Sign up to set email alerts
|

Top-down estimates of biomass burning emissions of black carbon in the Western United States

Abstract: Abstract. We estimate biomass burning and anthropogenic emissions of black carbon (BC) in the western US for MayOctober 2006 by inverting surface BC concentrations from the Interagency Monitoring of PROtected Visual Environment (IMPROVE) network using a global chemical transport model. We first use active fire counts from the Moderate Resolution Imaging Spectroradiometer (MODIS) to improve the spatiotemporal distributions of the biomass burning BC emissions from the Global Fire Emissions Database (GFEDv2). The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 100 publications
0
40
0
Order By: Relevance
“…Surface level BC and PM 2.5 concentrations in GEOS–Chem have been evaluated with in situ observations in the U.S. in numerous studies (Duncan Fairlie et al, 2007; Heald et al, 2012; Henze et al, 2009; Leibensperger et al, 2012; Mao et al, 2013, 2011; Park et al, 2003, 2004, 2006; Pye et al, 2009; Walker et al, 2012; Zhang et al, 2012). The initial BC estimates from Park et al (2003) showed decent skill in simulating seasonal annual average BC concentrations (R 2 from 0.68 to 0.82, slopes of reduced major axis regressions from 0.83 to 1.17) compared to observations from the 24 h average concentrations collected one out of 3 days at IMPROVE sites (Malm et al, 1994) (http://vista.cira.colostate.edu/improve).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface level BC and PM 2.5 concentrations in GEOS–Chem have been evaluated with in situ observations in the U.S. in numerous studies (Duncan Fairlie et al, 2007; Heald et al, 2012; Henze et al, 2009; Leibensperger et al, 2012; Mao et al, 2013, 2011; Park et al, 2003, 2004, 2006; Pye et al, 2009; Walker et al, 2012; Zhang et al, 2012). The initial BC estimates from Park et al (2003) showed decent skill in simulating seasonal annual average BC concentrations (R 2 from 0.68 to 0.82, slopes of reduced major axis regressions from 0.83 to 1.17) compared to observations from the 24 h average concentrations collected one out of 3 days at IMPROVE sites (Malm et al, 1994) (http://vista.cira.colostate.edu/improve).…”
Section: Methodsmentioning
confidence: 99%
“…The initial BC estimates from Park et al (2003) showed decent skill in simulating seasonal annual average BC concentrations (R 2 from 0.68 to 0.82, slopes of reduced major axis regressions from 0.83 to 1.17) compared to observations from the 24 h average concentrations collected one out of 3 days at IMPROVE sites (Malm et al, 1994) (http://vista.cira.colostate.edu/improve). More recently, GEOS–Chem BC simulations have been evaluated in the Western US by Mao et al (2011, 2013) for 2006, using a previous version of the GFED biomass burning inventory (van der Werf et al, 2006). Mao et al (2013) found the model performed well for locations at elevations less than 1 km above sea level, while performance at mountainous sites was strongly impacted by uncertainties in the biomass burning emissions as well as model resolution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3.1. The adjoint model has previously been used to constrain emissions of CO (Kopacz et al, , 2010, BC (Mao et al, 2014;Zhang et al, 2015b), and other aerosols and to identify sources of ozone (L. , BC (Kopacz et al, 2011), and other aerosols (Zhang et al, 2015a). In addition, the adjoint has also been used to estimate the sensitivity of direct radiative forcing to aerosol emissions .…”
Section: Geos-chem Adjoint Simulation Of Bcmentioning
confidence: 99%
“…Most of the fire emission inventories utilize active fire locations and burned area to estimate the trace gases and aerosol emissions released into the atmosphere (Mao et al, 2014). However, the temporal and spatial distribution of biomass burning emissions is affected by several sources of errors related, e.g., to the lack of detection of small fires during prescribed and agricultural burning.…”
Section: Introductionmentioning
confidence: 99%